Волшебные сказки - Родари Джанни (Золотая библиотека, 2002)
3-5 кл Экземпляры: аб. (2003) / Инвентарный номер: 47135 / Цена: / Сис.шифр: 84(4Ита)-4 / Авт.знак: Р 60 / ГРНТИ: 17.82.93 / ББК: 84(4Ита)-4